Shuttle swimming test in young water polo players: reliability, responsiveness and age-related value - Melchiorri, G.; Viero, V.; Triossi, T.; Padua, E.; Bonifazi, M. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: This study investigated the applicability of a sport-specific test, the Shuttle Swim Test, in young water polo players to measure RSA. The aims were: to assess the reliability and to measure the responsiveness of the SST in young water polo athletes, and to provide age-related values of SST.